If Not Now Then When? The Reality of Women's Representation in Politics and Administration in Bangladesh: A Qualitative Study - Sayem, Md. Abu; Rumi, Maruf Hasan; Islam, Md. Rakibul (CV. Literasi Indonesia, 2025)
The political landscape of Bangladesh presents a complex tapestry of progress and challenges regarding women's representation. This study aims to identify the status of women in the top political and administrative arena of Bangladesh and shed light on the factors that are responsible for such positions. The study employed an exploratory research design, utilizing a phenomenological research approach. The study followed the purposive sampling technique to collect 13 respondents, including members of parliament, cabinet members, local government representatives, and different political party members. The findings of the study depict that women's representation in the parliament and cabinet remains insignificant in making substantive decisions. Cultural and social structural barriers, muscle politics, and reluctance to adopt change by top political leadership are considered the main barriers in this regard. This research represents a distinctive addition to the interdisciplinary fields of gender studies and political science in Bangladesh, employing both primary and secondary data to arrive at a clear and definitive conclusion regarding the subject matter under investigation.